2018
DOI: 10.1001/jamanetworkopen.2018.0818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Automated Patient Dashboard Using Active Choice and Peer Comparison Performance Feedback to Physicians on Statin Prescribing

Abstract: Key Points Question Can an automated patient dashboard and nudges to physicians increase guideline-appropriate statin prescription rates among patients who were not previously receiving statin therapy? Findings In this cluster randomized clinical trial of 96 primary care physicians from 32 practice sites including 4774 patients, an automated patient dashboard using active choice framing and peer comparison feedback led to a modest but significant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 34 publications
2
125
0
Order By: Relevance
“…A previous systematic review found that the use of structured referral forms and the involvement of consultants in educational activities, both techniques employed here, improved referral appropriateness 24. More recent trials have found that the use of performance feedback methods, including peer comparison with active choice framing and audit and feedback reporting, as well as accountable justification, increased appropriate prescribing behaviour in primary care 25–27. The knowledge translation strategies employed here were primarily passive and may have been less effective than more active strategies 28 29.…”
Section: Discussionmentioning
confidence: 81%
“…A previous systematic review found that the use of structured referral forms and the involvement of consultants in educational activities, both techniques employed here, improved referral appropriateness 24. More recent trials have found that the use of performance feedback methods, including peer comparison with active choice framing and audit and feedback reporting, as well as accountable justification, increased appropriate prescribing behaviour in primary care 25–27. The knowledge translation strategies employed here were primarily passive and may have been less effective than more active strategies 28 29.…”
Section: Discussionmentioning
confidence: 81%
“…It should also be emphasized that the time involved in performing a consultation is independent of the quality of medical care provided, and while our study focused on the effect of the dashboard on consult TAT, this was not a guideline-based outcome that might accurately reflect quality of care, such as that studied in the PRESCRIBE cluster-randomized controlled trial. 41 Despite these limitations, we found that a 5-month decrease in inpatient neurological consultation TAT followed the neurological dashboard go-live at a large academic medical center, which persisted over the following 7 months. We cannot definitively conclude that introduction of the iNYP neurology dashboard resulted in reduced TAT, decreases in cognitive burden, or increases in face-to-face time with patients, but we demonstrated that significant numbers of neurological and nonneurological house staff used the dashboard.…”
Section: Limitationsmentioning
confidence: 77%
“…BE offers unique insights for the design of implementation strategies that target human decisionmaking constraints (i.e., cognitive heuristics) across settings. BE approaches have yielded notable effects in changing clinician practices in other health domains [29][30][31][32]. For instance, changing the default options in the electronic health record (EHR) has been found to increase the prescribing of generic medications over pricier, brand-name medicines [29].…”
Section: Leveraging Insights From Behavioral Economicsmentioning
confidence: 99%